2005
DOI: 10.1111/j.1744-6171.2005.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet Social Support for Parents: The State of Science

Abstract: Electronic forms of social support have the potential to meet the identified needs of parents for more social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 80 publications
(90 reference statements)
1
41
0
1
Order By: Relevance
“…In many cases, these individuals lack an understanding of the child’s diagnosis and resulting challenges. For emotional understanding and resources, parents have indicated that they prefer to connect with other parents of CSHCN who live in their geographic area and who have a child with the same or a similar diagnosis [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…In many cases, these individuals lack an understanding of the child’s diagnosis and resulting challenges. For emotional understanding and resources, parents have indicated that they prefer to connect with other parents of CSHCN who live in their geographic area and who have a child with the same or a similar diagnosis [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…A third important factor is peer-support, which was found to reduce parenting stress in parents of chronically ill children [24,25] and to reduce the number of parent–child conflicts concerning diabetes in families of a child with T1D [15]. Peer support is also related to better coping in parents of a chronically ill child [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Peer support is also related to better coping in parents of a chronically ill child [25,26]. It is suggested that healthcare professionals should be actively involved in organizing peer contact [15,27], for example by facilitating peer support groups [15] or by appointing mentor-peers [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…She concluded that parents will utilize Internet-based communications 12 and that in general there is great potential for electronic communication to meet the needs of parents seeking additional support mechanisms. 13 In fact, successful Internet support systems have been implemented for a variety of populations and health states, including maternity and parenting, 14-19 cancer, 20 diabetes, 21 mental health, 22 CKD, 10 and HIV. 23 Despite the positive outcomes reported in these studies, in each of these online systems the assessed outcomes were either an assessment of support, or an assessment of satisfaction without formal assessment of usability.…”
Section: Introductionmentioning
confidence: 99%